Pro Kontra Liberalisasi Pendidikan - Muhammad Idrus (Universitas Islam Indonesia, 2006)
The chances to study abroad in 1970s are more use for graduate program either master or PhD program. These chances are also use for secondary schools or pre-universities. Those phenomena happened in 1990s. But in recent time, to study abroad seem more opportunities. The consequencies of Indonesian participation as a member of World Trade Organization ( WTO) and that of the global competition to make this nation-should receive the entering of foreign universities. In this sense, should many foreign universities in Indonesia impact to developing Indonesian universities? Or conversely as the beginning of destructing Indonesian universities?